Verifikasi Alat Multimeter Digital untuk Deteksi Cepat Residu Insektisida dalam Sayuran - Asep Kurnia; Eman Sulaeman; Asep Nugraha Ardiwinata (Agrikultura, 2018)
ABSTRACTVerification of digital multimeter for rapid detection of insecticide residues on vegetablesThe instruments that usually used for detection of pesticide residues are Gas Chromatography (GC), High Performance Liquid Chromatography (HPLC), and Thin Layer Chromatography (TLC), however, these instruments are expensive, take time, and need a large number of chemicals. Therefore, it is needed to develop rapid method in analyzing pesticide residues. One instrument that is potential for rapid detection of pesticide residues is digital multimeter. This method uses resistance differences of electrical current on chemical compounds. The aim of this research was to assess capability of digital multimeter for rapid detection of insecticide residues on vegetables by the aspects of precision, accuracy, linearity, and detection limit. The research was conducted in IAERI laboratory, Laladon, Bogor on January to December 2012. Insecticide residues that detected were organochlorine and organophosphate on some vegetables of potato, cabbage, carrot, onion, chili, and cucumber. The results showed that precision values of digital multimeter for detection organochlorine and organophosphate residues on vegetables were 0.02 to 2.46%. Linearity values of digital multimeter for detection endrin on onion and potato, heptachlor on onion, BHC on cucumber, chlorphyriphos on potato and cabbage, and dichlorvos on cabbage were 0.81, 0.84, 0.95, 0.71, 0.95, 0.80 and 0.76, respectively. Accuracy values of digital multimeter for detecting endrin and dieldrin on onion, chlorphyriphos on potato and cabbage, and profenophos on chili were 106.93%, 115.08%, 72.89%, 72.40%, and 98.06%, respectively. Detection and quantification limits of digital multimeter for detecting organochlorine were 0.08 to 0.17 ppm and 0.27 to 0.56 ppm, respectively. Meanwhile, detection and quantification limits of digital multimeter for detecting organophosphate were 0.05 to 0.27 ppm and 0.16 to 0.90 ppm, respectively. This result showed that digital multimeter was accurate and representative instrument for detecting pesticide residues on vegetables.Keywords: Digital Multimeter, Pesticides residue, VegetablesABSTRAKAlat yang digunakan untuk analisis residu pestisida antara lain Kromatografi Gas (KG), Kromatografi Cair Kinerja Tinggi (KCKT), Kromatografi Lapis Tipis (KLT), namun alat tersebut sangat mahal, dan perlu proses cukup lama serta memerlukan bahan kimia yang banyak. Untuk itu perlu dikembangkan metode cepat analisis residu pestisida. Salah satu alternatif deteksi cepat residu pestisida adalah dengan menggunakan Alat Multimeter Digital (AMD). Teknik analisis ini menggunakan prinsip perbedaan resistensi (tahanan) terhadap arus listrik dari senyawa kimia residu pestisida. Percobaan ini bertujuan mengetahui cara kerja awal AMD untuk deteksi cepat residu insektisida pada tanaman sayuran dari aspek presisi, akurasi, linearitas, dan limit deteksi. Penelitian dilaksanakan di Laboratorium Balai Penelitian Lingkungan Pertanian (Balingtan) di Laladon Bogor, mulai bulan Januari hingga Desember 2012. Residu insektisida yang dideteksi adalah organoklorin dan organofosfat pada beberapa sayuran yaitu kentang, kubis, wortel, bawang merah, cabe merah dan mentimun. Hasil penelitian menunjukkan bahwa nilai presisi AMD dalam mendeteksi organoklorin dan organofosfat pada sayuran berkisar 0,02-2,46%. Nilai linearitas AMD dalam mendeteksi endrin pada bawang merah dan kentang, heptaklor pada bawang merah, BHC pada mentimun, klorpirifos pada kentang dan kubis, serta diklorfos pada kubis masing-masing sebesar 0,81, 0,84, 0,95, 0,71, 0,95, 0,80 dan 0,76. Nilai akurasi AMD dalam mendeteksi endrin dan dieldrin pada bawang merah, klorpirifos padakentang dan kubis, serta profenofos pada cabe merah masing-masing sebesar 106,93 %, 115,08%, 72,89 %, 72,40%, dan 98,06%. Nilai LOD (limit deteksi) dan LOQ (limit quantifikasi) AMD terhadap organoklorin berkisar antara 0,08-0,17 ppm dan 0,27-0,56 ppm, sedangkan terhadap golongan organofosfat berkisar antara 0,05-0,27 ppm dan 0,16-0,90 ppm. Hasil penelitian ini menunjukkan bahwa AMD merupakan alat yang cukup akurat dan representatif untuk deteksi cepat residu pestisida pada sayuran.Kata Kunci: Alat Multimeter Digital, Residu pestisida, Sayuran